Altered Relative Expression of BMPs and BMP Inhibitors in Cartilaginous Areas of Human Fractures Progressing towards Nonunion - Kwong, Francois N.K. (J Orthop Res, 2009)
The present study was conducted to evaluate the hypothesis that an imbalance in the local production of bone morphogenetic proteins (BMPs) and BMP inhibitors exists within the cartilaginous intermediate of nonhealing fractures. Biopsies were recovered intraoperatively from human fractures that, upon follow-up, were found to heal normally or become nonunions. The samples were examined by immunohistochemistry to determine the expression of BMP-2, BMP-14, and the BMP inhibitors noggin and chordin. Expression was determined semiquantitatively based on the area of positive staining per area of cartilage and by determining the number of positively staining cells and the intensity of staining. There was a significant reduction in BMP-2 and BMP-14 expression in cartilaginous areas of nonhealing fractures compared to healing fractures. However, there was no difference in the expression of the BMP inhibitors between the two groups of fractures. This imbalance in the expression of BMPs and BMP inhibitors within cartilaginous areas of developing nonunions may account for their reduced bone forming ability. These data suggest strategies for preventing the development of nonunions by altering levels of BMPs and their inhibitors within fracture sites.